Dependency of running shoe preference on assessment method and cultural background - Lim, Chen Yen. (2013)
The Visual Analog Scale (VAS) has been widely used in footwear perception studies due to its sensitivity and unbiased results. However, in retail stores, heads-on comparison, which is wearing two different shoes at a time, would be a more commonly used method to select the preferred running shoes. This study aims to examine the influence of assessment method and cultural background between Singapore and China on running footwear perception. A total of 100 participants, 50 from each country, tested 4 shoes for 2 assessment methods – VAS and heads-on comparison – on the treadmill. Each pair were assessed for 5 minutes based on fit, cushioning, arch support, stability and overall shoe preference for the VAS. For heads-on comparison, 6 different combinations were assessed for 1 minute each based on overall shoe preference. Moderate to good reliability were concluded for the VAS assessment, and fair to moderate reliability for the heads-on comparison. For the whole results, the numbers of matched shoe ranking between the assessment methods are low. A general trend was observed that Shoe B and D were preferred over Shoe A, and Shoe C was least preferred for both countries. A wider range was also used by the Singaporeans, but maximum and minimum values used for the VAS were lower than the Beijing Chinese. In conclusion, running footwear perception differs between assessment methods. Similar preferences were observed for subjects from both countries; running footwear perception does not differ between cultural backgrounds. Lastly, running footwear discrimination range differs between Beijing and Singapore.